The Effect of Non-Performing Loans, Return on Assets, and Operating Expenses to Operating Income on Financial Distress: An Analysis Using the Zmijewski (X-Score) Method - Rollis Ayu Ditasari; Arief Eko Saputro (Citakonsultindo, 2026)
Financial Distress is a condition where a company is in financial difficulty and can end in bankruptcy. The object of this study is the People's Credit Banks throughout the Madiun Residency. The purpose of this study is to prove the effect of Non-Performing Loans, Return on Assets and Operating Income Expenses on Financial Distress. The secondary data source used in this study is the company's financial statements. The population in this study is the People's Credit Bank companies throughout the Madiun Residency registered with the OJK for the 2020-2024 period, using the Purposive Sampling method with a sample size of 22 company. The method in this study uses a quantitative approach using SPSS 25 software. The results of this study are that Non Performing Loans have a positive and significant effect on Financial Distress, Return on Assets has a negative and significant effect on Financial Distress, Operating Income Expenses have a positive and significant effect on Financial Distress and Non Performing Loans, Return on Assets and Operating Expenses and Operating Income have a simultaneous effect on Financial Distress.